Hypertransaminasemia: Incidence and its Clinical Correlations in Patients with COVID-19 Infection - Asreah, Rabah H.; Al Hussein, Ali A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: coronavirus-19 disease recently emerged as a global pandemic affecting the respiratory system. However, during the course of the illness, the disease can directly or indirectly involve other body organs including the liver. Objectives: This study aimed to determine the incidence of hepatic involvement and its clinical significance in COVID-19 patients. Patients and Methods: This cross-sectional single-center study was conducted on 112 patients who have an infection with Covid 19 (proved by polymerase chain reaction). Depending on infection severity, patients were categorized into three groups (according to the guidelines of the Chinese National Health Committee): mild, moderate, and severe cases. Blood samples were collected from each patient and liver function tests were conducted. Abnormal hepatic enzyme was considered when any enzyme (alanine transaminase, aspartate transaminase, and alkaline phosphatase) was more than the upper normal laboratory value. Categorical variables were presented as numbers and percentages and analyzed with a Chi-square test. A P≤ 0.05 was considered statistically significant. Results: Sixty-six patients (58.93%) had normal liver enzymes, while the other 46 (41.07%) had abnormal liver enzymes. The mean age of patients with elevated liver enzymes was 45.17±11.93 years which was significantly higher than that of normal liver enzymes patients (38.92±13.47 years). In severe cases, 45.65% of patients had elevated liver enzyme compared with 43.48% in moderate group and 10.87 % in mild group. Conclusions: Acute liver injury as indicated by hypertransaminasemia is a frequent finding in COVID-19 patients. Elderly patients with moderate to severe COVID-19 are more prone to hepatic involvement. Received: May, 2022 Accepted: July, 2023 Published: Jan 2024